Teaching others rule-use improves executive function and prefrontal activations in young children - Moriguchi, Yusuke; Sakata, Yoko; Ishibashi, Mikako; Ishikawa, Yusuke (Frontiers in Psychology, 2015)
Intervention of executive function during early childhood is an important research topic. This study examined the effect of a child-friendly intervention program, where children interacted with a doll or a puppet. Children were presented with cognitive shifting tasks before and after an intervention. In the intervention, children interacted with a doll or a puppet, and taught rules of the cognitive shifting tasks to the object. As the results, 3- to 5-year-old children significantly improved the performances and strengthened activations in the lateral prefrontal regions as measured by near-infrared spectroscopy. The results suggest that interaction with a doll or a puppet may have a significant impact on the development of executive function.